Effect and safety of extracorporeal shockwave therapy for postherpetic neuralgia: A randomized single-blind clinical study - Chen, Lu; Qing, Ailing; Zhu, Tao; Yang, Pingliang; Ye, Ling (Frontiers in Neurology, 2022)
Objective To evaluate the efficacy and safety of extracorporeal shockwave therapy (ESWT) for postherpetic neuralgia. Design Randomized single-blind clinical study. Patients Patients with postherpetic neuralgia. Methods Patients were randomly divided into the control group and the ESWT group. The control group received conventional treatment while the ESWT group received conventional treatment and ESWT. The primary outcome is pain degree as assessed by the numeric rating scale (NRS), and secondary outcomes include brief pain inventory (BPI), Self-rating Anxiety Scale (SAS), Self-rating Depression Scale (SDS), and Pittsburgh Sleep Quality Index (PSQI). Data were collected at baseline and at weeks 1, 4, and 12. Linear mixed-effects models were applied to repeated measurement data. Results The scores on the NRS, BPI, SAS, SDS, and PSQI decreased over time in both groups. The NRS and SDS scores of the ESWT group were statistically lower than the control group. There was no time × group interaction in the mixed model analysis. Baseline age was correlated with NRS scores and BPI scores, and invasive treatment was related to PSQI scores, with no interaction effect for baseline confounders observed. No adverse events were observed during the process of this trial. Conclusion Extracorporeal shockwave therapy combined with conventional treatment could relieve pain and improve the psychological state in patients with postherpetic neuralgia without serious adverse effects.